2017
DOI: 10.1177/1750698017714835
|View full text |Cite
|
Sign up to set email alerts
|

How did you hear the news? The role of traditional media, social media, and personal communication in flashbulb memory

Abstract: Flashbulb memories are at the intersection of public and private event memory. We investigated whether the source of news (traditional media, social media, or another person) shaped how people remembered learning of an event. Individuals were asked how they learned of Osama bin Laden’s assassination immediately after the event and 7, 42, 224, or 365 days later. Initial memory reports from those who learned from traditional media showed enhanced phenomenological features (i.e., a sense of recollection and vivid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Although the diagnosis news itself may be similarly surprising and consequential across patients, there may be significant differences in how news of a diagnosis is delivered , depending on the medical professional. Prior work has shown that news source can influence how an event is remembered (Bohannon, Gratz, & Cross, 2007; Schaefer, Halldorson, & Dizon‐Reynante, 2011; Schmolck et al, 2000; Talarico, Kraha, Self, & Boals, 2019). In the current study, we expand these findings to determine whether the way in which the news is delivered is related to the likelihood and persistence of a FBM.…”
Section: Introductionmentioning
confidence: 99%
“…Although the diagnosis news itself may be similarly surprising and consequential across patients, there may be significant differences in how news of a diagnosis is delivered , depending on the medical professional. Prior work has shown that news source can influence how an event is remembered (Bohannon, Gratz, & Cross, 2007; Schaefer, Halldorson, & Dizon‐Reynante, 2011; Schmolck et al, 2000; Talarico, Kraha, Self, & Boals, 2019). In the current study, we expand these findings to determine whether the way in which the news is delivered is related to the likelihood and persistence of a FBM.…”
Section: Introductionmentioning
confidence: 99%
“…Students actively participate in learning as it is not one-way. Instructional media is very supportive of students in their memory and understanding (Talarico, Kraha, Self & Boals, 2019). Every learning activity is emphasized to facilitate students in understanding the subject matter.…”
Section: Resultsmentioning
confidence: 99%
“…The emergence of self-media has its historical inevitability, and the self-media is also a double-edged sword. Promoting the development of the news business but also to the mainstream media has caused varying degrees of impact, causing changes and innovations in the traditional media structure [7][8][9] In the self-media environment, the mainstream media news dissemination audience will be affected to some extent. The current self-media can also be called the national DIY; that is, more netizens are able to participate in it, hand to publish media news, which is also a rare feature of self-media.…”
Section: Introductionmentioning
confidence: 99%